PENERAPAN PSAK NO. 2 TENTANG LAPORAN ARUS KAS DALAM PENGAMBILAN KEPUTUSAN PADA PERUM BULOG DIRVE SULUT DAN GORONTALO - Syaefudin, Fanesa Isalia Minanda; Morasa, Jenny; Alexander, Stanly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2015)
In the company’s Financial Statements is a means of consideration in decision making so that, componentsin the financial statements must betrue and correct. In thedecision making companies should use the cash Flow Statement because sometimes the income and balance sheet does not show the real state of corporate finance. The purposeof this study to determine the application of the Cash Flow Statement in accordance with SFAS No. 2 in corporate decision. This type of research is quantitative descriptive. The results showed, net cash provided by the company during the year has decreased compared to the previous year. This study uses the ratio analysisin corporate decision making. The Ratio of Operating Cash Flow to Total Liabilities can be used as basis for decision making in the company repay its total Liability for one year of operation. The Ratio of Cash Flow to Current Liabilities can be used as the basis of the decision making companies when measuring the company’s ability to pay Current Liabilities by Net Operating Cash Flow. The Ratio of Cash Flow to Sales companies measure the company’s ability to measure the company’s ability to obtain cash from to sale. Leaders should Perum Bulog particularly the finance department needs to implement the Cash Flow Statement as the basis of its analysis so that can know the financial situation and can be used as a basis for decision making of the company.